Dynamic maternal gradients and morphogenetic networks in Drosophila early embryo. (November 2018) - Surkova, Svetlana; Golubkova, Elena; Mamon, Ludmila; Samsonova, Maria
Abstract: Here, we review the latest publications on dynamics and interpretation of morphogen gradients in Drosophila early embryo. The instructive cues provided by these gradients are further interpreted by target genes to enable correct cell fate specification. Moreover, recent studies point on the dynamic and active input from gradients themselves. Latest research has demonstrated that the decay of maternal gradients affects the positional dynamics of target gap gene expression. Study of temporal interpretation of the Bicoid (Bcd) morphogen signal revealed that the Bcd-dependent cell fate specification proceeds sequentially from the posterior towards the anterior. The 'morphogenetic network' of maternal and zygotic regulators functions to spatially organize expression of Bcd-dependent target genes. The analysis of molecular mechanisms of Bcd interaction with target enhancers showed that Bcd gradient induces different chromatin states depending on its concentration. All these findings significantly update the model of morphogen gradient interpretation and provide new perspectives to uncover mechanisms of pattern formation in early embryogenesis.